Combined effect of supported and unsupported sleepers on lateral ballast resistance in ballasted railway track. (January 2023) - Xu, Chong; Ito, Kazuki; Hayano, Kimitoshi; Momoya, Yoshitsugu
Abstract: The lateral resistance of a ballast bed significantly affects the lateral stability of ballasted railway tracks. Hence, a precise evaluation of the lateral ballast resistance is essential for predicting rail buckling potential. Differential ballast settlement can cause the sleeper bottom to separate from the ballast, thereby causing the sleeper to become an "unsupported sleeper" suspended from the rail. The gap between the ballast and sleeper bottom results in zero frictional force at the bottom, which reduces the lateral ballast resistance. However, sleepers near unsupported sleepers are subjected to the additional weight of the unsupported sleepers and the rail load borne by the unsupported sleepers. Consequently, they become over-supported. Additional loads may change the lateral ballast resistance of the supported sleepers. Previous studies did not consider the combined effects of supported and unsupported sleepers on the lateral ballast resistance. Therefore, in this study, experiments are conducted on 1/5-scale ballasted track models to investigate these combined effects. Analytical methods for evaluating the lateral ballast resistance when panels incorporate both supported and unsupported sleepers are presented. Pullout tests conducted on panels incorporating supported and unsupported sleepers reveal that unsupported sleepers adversely affect the lateral ballast resistance. The lateral ballast resistance decreases as the number of unsupported sleepers increases, irrespective of sleeper type. Moreover, the analytical results reveal that the lateral ballast resistance of the panel is underestimated when only the decrease in the lateral ballast resistance due to unsupported sleepers is considered. Meanwhile, the analyses considering the combined effects of supported, unsupported, and over-supported sleepers provide reasonable estimates of the lateral ballast resistance, similar to the experimental results. This indicates the importance of comprehensively considering the effects of the support conditions of the sleepers on the lateral ballast resistance to estimate rail buckling potential.